Thymoquinone Enhances Doxorubicin Efficacy via RAS/RAF Pathway Modulation in Ovarian Adenocarcinoma - Veysel Toprak; İlhan Özdemir; Şamil Öztürk; Orhan Yanar; Yusuf Ziya Kizildemir; Mehmet Cudi Tuncer (Pharmaceutics)
Background/Objectives: Ovarian cancer remains one of the most commonly diagnosed malignancies among women worldwide. The heterogeneity among tumor subtypes and the emergence of treatment resistance have raised significant concerns regarding the long-term efficacy of chemotherapy, radiotherapy, and immunotherapy. In response to these challenges, drug repurposing strategies—utilizing existing drugs in novel therapeutic contexts—have gained increasing attention. This study aimed to investigate the cytotoxic and apoptotic effects of the combined application of doxorubicin (DX) and thymoquinone (TQ) on ovarian adenocarcinoma cells (OVCAR3). Methods: OVCAR3 cells were cultured in RPMI medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin. Cell viability and proliferation were assessed using the MTT assay following treatment with various concentrations of DX and TQ. NucBlue immunofluorescence staining was employed to examine nuclear morphology and to identify apoptosis-associated changes. Additionally, quantitative real-time polymerase chain reaction (qRT-PCR) was per-formed to evaluate the expression levels of apoptosis-related and oncogenic pathway genes, including RAF, RAS, Bcl-2, and Bax. Results: The results demonstrated that the combination of DX and TQ significantly reduced OVCAR3 cell viability and induced apoptosis in a dose-dependent manner. qRT-PCR analysis revealed a downregulation of RAS, RAF, and Bcl-2 expression, along with an upregulation of Bax, indicating activation of the intrinsic apoptotic pathway. These findings suggest that thymoquinone exerts an-ti-proliferative and pro-apoptotic effects by modulating the RAS/RAF signaling cascade. Furthermore, the co-administration of thymoquinone with doxorubicin potentiated these effects, suggesting a synergistic interaction between the two agents. Conclusions: Histopathological and molecular evaluations further confirmed the activation of apoptosis and the suppression of key oncogenic pathways. Collectively, these results underscore the therapeutic potential of thymoquinone as both a monotherapy and an adjuvant to conventional chemotherapy, warranting further validation in preclinical and clinical studies.